Business Development and Management Strategies for Badan Usaha Milik Desa (BUMDes) Raharja, Desa Rancaekek Wetan, Kecamatan Rancaekek, Kabupaten Bandung - et. al., Rizal R. Padmakusumah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article is the result of research as well as one of the outcomes of Community Service activities in Rancaekek Wetan Village, Rancaekek District, Bandung Regency. The object of this research is a statet-owned enterprise (village scope or level), namely BUMDes Raharja. The purpose of this research and PKM is to help BUMDes Raharja to be even better in terms of business development and managerial abilities. The research method used is descriptive qualitative data collection methods, namely interviews-observations and analysis tools using focus group discussion (FGD). The results showed that BUMDes Raharja has good business and management potential if it is able to make various changes or adjustments. Suggestions from the research on PKM results are to develop its business, Raharja BUMDes can use 3 alternative strategic options, namely: (1) horizontal integration, (2) concentric diversification, and (3) conglomerate diversification. Other suggestions are: (1) BUMDes Raharja can create an annual short-medium term planning system, (2) separate management and employee or staff status if the organization grows larger, (3) leaders have a large vision and influence, and (4) a system organizational control is made systematic and up-to-date.